Penguatan Metode Computational Thinking untuk Guru Madrasah dalam Rangka Meningkatkan Minat Belajar Siswa Pasca Pandemi Covid-19 - Kustomo; Lulu Choirun Nisa; Hery Mustofa (Universitas Muhammadiyah Surakarta, 2023)
Madrasah teachers are currently considered to have lower cognitive competence when compared to formal school teachers in general, although this statement is not entirely correct. Researchers have conducted computational thinking training in several madrasa of Central Java Provinces, like MIN 1 Kendal, MTs N 1 Jepara, and MAN 1 Grobogan. Computational Thinking (CT) involves problem solving and system design by breaking it down into several stages that are effective, efficient, and comprehensive, including decomposition, pattern recognition, abstraction, and algorithms which are some of the basic concepts of computer science. The purpose of this study is the implementation of CT by madrasa’ teachers on each lesson to students in order to increase student learning interest. The research method used is blended learning which is a combination of an online course (introduction to Bebras Indonesia and CT) and an onsite course (training on CT and implementation of CT to students). The results showed that there was an increase in the average score of the trainees between the pre-test and post-test of the teachers at MIN 1 Kendal, MTs N 1 Jepara, and MAN 1 Grobogan i.e. 70.23%, 70.01% and 80. 64%, respectively. Furthermore, student testimonials after the implementation of CT in subjects taught by the majority of teachers at 66.79% filled in very interesting so that CT learning was very effective in increasing student learning interest in madrasah.